2017
DOI: 10.1136/bmjsem-2017-000230
|View full text |Cite
|
Sign up to set email alerts
|

No effects of functional exercise therapy on walking biomechanics in patients with knee osteoarthritis: exploratory outcome analyses from a randomised trial

Abstract: AimTo assess the effects of a functional and individualised exercise programme on gait biomechanics during walking in people with knee OA.MethodsSixty participants were randomised to 12 weeks of facility-based functional and individualised neuromuscular exercise therapy (ET), 3 sessions per week supervised by trained physical therapists, or a no attention control group (CG). Three-dimensional gait analyses were used, from which a comprehensive list of conventional gait variables were extracted (totally 52 kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 10 publications
(32 reference statements)
0
14
1
1
Order By: Relevance
“…For all the included RCT studies 14 17 , 25 , the total scores of the PEDro scale were higher than 5 points, thus defined as high quality. Based on the NIH scale, the overall quality rating of the included non-RCT studies 18 , 26 , 27 was "Good" (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all the included RCT studies 14 17 , 25 , the total scores of the PEDro scale were higher than 5 points, thus defined as high quality. Based on the NIH scale, the overall quality rating of the included non-RCT studies 18 , 26 , 27 was "Good" (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have pointed out that resistance training may be able to improve the gait velocity of knee OA patients by increasing the strength of the quadriceps 14 16 . On the contrary, a few others showed that resistance training failed to improve the gait velocity of knee OA patients 17 , 18 . The difference in outcomes could be possibly due to the small sample size or different interventions in the studies 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While exercise interventions have consistently demonstrated improvements in the pain and function of knee OA patients, identifying concomitant changes in gait patterns has been rarely reported using conventional group-based methods [ 39 , 40 , 41 , 42 ]. Given that much of this research has examined single, discrete variables (e.g., knee adduction moment), the sensitivity of this type of univariate statistical approaches is questionable [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these multivariate changes often remain limited when assessed in conventional group-based analyses [ 44 ]. This further suggests that exercise interventions may not elicit any consistent change in gait patterns, univariate or multivariate, across heterogeneous diseases such as knee OA [ 39 , 40 , 41 , 42 ]. Therefore, a significant strength of the current study is the introduction of an alternative, single-subject model to track multivariate, multi-segment changes in gait biomechanics.…”
Section: Discussionmentioning
confidence: 99%